IN VITRO PROPAGATION OF KULO VARIETY CHRYSANTHEMUM NODULE EXPLANTS IN MURASHIGE AND SKOOG MEDIA WITH NAPHTALENE ASETIC ACID AND BENZILAMAMINO PURINE - WENNY TILAAR (International Journal of Pharma and Bio Sciences, 2014)
The purpose of this study was to obtain new buds of kulo chrysanthemum by in vitro propagation technique or in vitro multiplication. It’s also aimed to discover the influence of NAA and BAP in kulo chrysanthemum bud multiplication. This study used completely randomized design which was arranged by factorial with treatments which consisted of 0 ppm ; 0,5 ppm ; 1 ppm of NAA which were combined with 1 ppm ; 2 ppm ; 3 ppm of BAP. The explants used were kulo chrysanthemum nodules. Observed variables consisted of: budding time, callusing time, number of buds, height of buds, number of leaves, umber of roots, length of roots, percentage of grown cultures, percentage of unresponsive cultures, percentage of contaminated cultures. Data was analyzed using analysis of variance and continued by 5 % LSD test. The result was that there were interactions between NAA and BAP in their influence on number of buds, height of buds, number of roots, root length. NAA and BAP individually influenced the number of leaves.